2018
DOI: 10.1186/s12887-018-1256-y
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine is effective and safe during NIV in infants and young children with acute respiratory failure

Abstract: BackgroundNoninvasive ventilation (NIV) is increasingly utilized in infants and young children, though associated with high failure rates due to agitation and poor compliance, mostly if patient-ventilator synchronization is required.MethodsA retrospective cohort study was carried out in an academic pediatric intensive care unit (PICU). Dexmedetomidine (DEX) was infused as unique sedative in 40 consecutive pediatric patients (median age 16 months) previously showing intolerance and agitation during NIV applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
(38 reference statements)
2
17
0
3
Order By: Relevance
“…This effect is possibly mediated via its sedative and analgesic properties. Dexmedetomidine provides analgesia via receptors in the spinal cord, and attenuation of the stress response [28]. As shown in previous studies [13,14], we also found that premedication with intranasal dexmedetomidine reduced the patients' separation anxiety and resulted in more satisfactory tolerance of the facial mask during anesthesia induction.…”
Section: Discussionsupporting
confidence: 86%
“…This effect is possibly mediated via its sedative and analgesic properties. Dexmedetomidine provides analgesia via receptors in the spinal cord, and attenuation of the stress response [28]. As shown in previous studies [13,14], we also found that premedication with intranasal dexmedetomidine reduced the patients' separation anxiety and resulted in more satisfactory tolerance of the facial mask during anesthesia induction.…”
Section: Discussionsupporting
confidence: 86%
“…This effect is possibly mediated via its sedative and analgesic properties. Dexmedetomidine provides analgesia via receptors in the spinal cord, and attenuation of the stress response [25]. As shown in previous studies [10, 11], we also found that premedication with intranasal dexmedetomidine reduced the patients’ separation anxiety and resulted in more satisfactory tolerance of the facial mask during anesthesia induction.…”
Section: Discussionsupporting
confidence: 83%
“…Studies have shown that procedural sedation and analgesia as a salvage strategy are both safe and effective for patients intolerant to NIV (8)(9)(10)(11). However, to date, there is no consensus on sedation protocols for such patients (12).…”
Section: Introductionmentioning
confidence: 99%